An ecological momentary assessment of the effect of fasting during Ramadan on disordered eating behaviors. (1st August 2018) - Chia, Jia Li Pauline; Fuller-Tyszkiewicz, Matthew; Buck, Kimberly; Chamari, Karim; Richardson, Ben; Krug, Isabel
Abstract: Dietary restriction contributes to disordered eating (DE) behaviors and associated cognitions. However, it is unclear how these outcomes are impacted by dietary restriction for religious purposes, such as fasting observed by Muslims during Ramadan. Using ecological momentary assessment, this study assessed the impact of Ramadan fasting on DE behaviors and correlates. Muslim participants fasting during Ramadan ( n  = 28) and a control group of non-fasting participants ( n  = 74) completed baseline measures assessing demographic characteristics and eating pathology. A mobile phone application then prompted participants six times per day for seven days to self-report on dietary restriction efforts, body satisfaction, temptation to eat unhealthily, feelings of guilt or shame following food, and DE behaviors including bingeing, vomiting, and other purging behaviors (use of laxatives, diuretics, or diet pills). After controlling for eating pathology, multilevel modeling indicated that, as expected, the Ramadan fasting group spent significantly more time restricting food intake than the non-fasting group. The Ramadan fasting group also experienced significantly greater temptation to eat unhealthily than their non-fasting counterparts. However, this difference disappeared once models were adjusted for differences in time spent restricting food intake. There were no other significant differences between the groups on any DE variables. These findings suggest that while dietary restriction for health or appearance-related reasons is a known contributor to DE, dietary restriction for religious purposes, such as that observed during the practice of Ramadan, may not confer increased risk of DE symptoms.